Bonsoir,
Factoriser les expressions suivantes :
A = 3x + 12
A = 3*x + 3*4
A = 3(x + 4)
B = x² + 6x
B = x*x + x*6
B = x(x + 6)
C = 8x² + 24
C = 8*x² + 8*3
C = 8(x² + 3)
D = 9x² - 64
D = (3x)² - 8²
→ identité remarquable :
D = (3x - 8)(3x + 8)
E = 100 - 25x²
E = 25*4 - 25*x²
E = 25(-x² + 4)
F = 7(5 - 4x) - (5 - 4x)(3 - 5x)
F = 7(5 - 4x) - (5 - 4x)(3 - 5x)
F = (5 - 4x)(7 - (3 - 5x))
F = (5 - 4x)(7 - 3 + 5x)
F = (5 - 4x)(5x + 4)
G = (7x + 2)² - 4x(7x + 2)
G = (7x + 2)(7x + 2) - 4(7x + 2)
G = (7x + 2)(7x + 2 - 4)
G = (7x + 2)(7x - 2)
H = 16x² - (2x + 1)²
H = (4x)² - (2x + 1)²
→ identité remarquable :
H = (4x - (2x + 1))(4x + (2x + 1))
H = (4x - 2x -1)(4x + 2x + 1)
H = (2x - 1)(6x + 1)
* = multiplication
Bonne soirée.